IMPROVING ENGLISH TENSE VERBS THROUGH CARTOON FILM AT THE FIRST YEAR OF JUNIOR HIGH SCHOOL STUDENTS - Natalia Manuhutu (Universitas Musamus, 2018)
This research aimed at finding out the use of cartoon film in improving the students’ English tense verbs. To explain the improvement, the researcher used experimental research method. The population of the research consists of 210 students and took 60 students as a sample which was conducted two classes: 30 students in experimental class and 30 students in control class. The research data are collected using vocabulary test in multiple choice items, matching test and completion test which is analyzed by descriptive and inferential statistic through SPSS 21.0. The location of this research was taken at the first year students’ of SMP Negeri 9 Ambon. The result data analysis are mean score of posttest of experimental class is higher than control class in vocabulary (73.8 > 66.2).The different of those mean score is statistically significant, it is based on t-test value at significant level 0.05, the probability value is lower than significant level ( 2.021 < 32.68 ). Based on the result above, the researcher concluded that using cartoon film to improve the students’ English tense verbs of the first year of SMP Negeri 9 Ambon was effective because the data shows a very significant different between t- test and t- table. Keywords: cartoon film; English tense verbs; improving